Do Credit Shocks Matter? : A Global Perspective - Helbling, Thomas (IMF Working Papers; Working Paper ;, 2010)
This paper examines the importance of credit market shocks in driving global business cycles over the period 1988:1-2009:4. We first estimate common components in various macroeconomic and financial variables of the G-7 countries. We then evaluate the role played by credit market shocks using a series of VAR models. Our findings suggest that these shocks have been influential in driving global activity during the latest global recession. Credit shocks originating in the United States also have a significant impact on the evolution of world growth during global recessions.